Lowering missing item values in quality-of-life questionnaires: an interventional study - Müller-Bühl, Uwe; Franke, Bernhard; Krug, Katja; Engeser, Peter (International journal of public health, 2011)
Missing item values (MIV) often occur in quality-of-life (QoL) questionnaires. This study aimed to examine whether the use of introductory exemplary questions reduces the number of MIV and what patient-related factors influence effectiveness of such a QoL form training.